A real-time PCR for specific detection of the Legionella pneumophila serogroup 1 ST1 complex. (April 2020) - Ginevra, C.; Chastang, J.; David, S.; Mentasti, M.; Yakunin, E.; Chalker, V.J.; Chalifa-Caspi, V.; Valinsky, L.; Jarraud, S.; Moran-Gilad, J.; ,
Abstract: Objective: Legionella pneumophila serogroup 1 ( Lp 1) sequence type (ST) 1 is globally widespread in the environment and accounts for a significant proportion of Legionella infections, including nosocomial Legionnaires' disease (LD). This study aimed to design a sensitive and specific detection method for Lp ST1 that will underpin epidemiological investigations and risk assessment. Methods: A total of 628 Lp genomes (126 ST1s) were analyzed by comparative genomics. Interrogation of more than 900 accessory genes revealed seven candidate targets for specific ST1 detection and specific primers and hydrolysis probes were designed and evaluated. The analytical sensitivity and specificity of the seven primer and probe sets were evaluated on serially diluted DNA extracted from the reference strain CIP107629 and via qPCR applied on 200 characterized isolates. The diagnostic performance of the assay was evaluated on 142 culture-proven clinical samples from LD cases and a real-life investigation of a case cluster. Results: Of seven qPCR assays that underwent analytical validation, one PCR target ( lpp1868 ) showed higher sensitivity and specificity for ST1 and ST1-like strains. The diagnostic performance of the assay using respiratory samples corresponded to a sensitivity of 95% (19/20) (95% CI (75.1–99.9)) and specificity of 100% (122/122) (95% CI (97–100)). The ST1 PCR assay could link two out of three culture-negative hospitalized LD cases to ST1 during a real-time investigation. Conclusion: Using whole genome sequencing (WGS) data, we developed and validated a sensitive and specific qPCR assay for the detection of Lp 1 belonging to the ST1 clonal complex by amplification of the lpp1868 gene. The ST1 qPCR is expected to deliver an added value for Lp control and prevention, in conjunction with other recently developed molecular assays.